The Effect of Health Education Using Flash Card Media on Adolescent Reproductive Health Behavior - Maulana, Ghonim; Kustin (Al-Hijrah Indonesia, 2025)
Adolescent problems related to reproductive health are generally caused by a lack of knowledge about sexual and reproductive health, which negatively impacts their reproductive health condition. Currently, many adolescents face issues such as contracting Sexually Transmitted Infections (STIs), HIV (Human Immunodeficiency Virus), AIDS (Acquired Immune Deficiency Syndrome), as well as unplanned pregnancies. Therefore, education tailored to the characteristics of adolescents is essential, one of which can be done through flash cards as a medium for health education. This study aims to determine how using flash card media affects adolescent behavior in maintaining reproductive health. The study uses a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The sampling technique used cluster sampling, with 40 respondents consisting of 20 individuals in the intervention group and 20 in the control group, all from SMPN 1 Rambipuji. Data were analyzed using univariate and bivariate analysis. Statistical analysis using the Wilcoxon Test showed a significant difference between the pre-test and post-test scores in both the intervention and control groups, with a p-value of 0.000 (< 0.05). In addition, the Mann-Whitney Test also showed a p-value of 0.000 (< 0.05), indicating a significant effect of flash card usage on changes in reproductive health behavior among adolescents. These findings suggest that routine use of flash cards, for example, once a week for a month, is efficacious in improving adolescent behavior in maintaining their reproductive health.